Sunteți pe pagina 1din 21

# 1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Geometric
A geometric progression is
Progression is a
alsoisknown
What a as a geometric
sequence of
sequence, and inaccurately,
Geometric numbers in
as a geometric series which any term
Progression?
can be obtained
from the
previous term by
multiplying by a
certain fix
number called
the common
1 2 3 4 5
ratio
6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
The general term of a geometric sequence is given by

Tn = a r n - 1

## The common ratio, r is given by

T2 T3 Tn
r = = = ...=
T1 T2 T n-1

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Solution :
Example 2 :
T1 = 27 , T2 = 9 , T3 = 3
Find the 9th term
r = 9 = of1 the geometric
sequence 27 27 , 9 3, 3 , . . .
T n = a r n-1
T9 = ar8
= ( 27 ) 1 8

3
= 33
38
= 1 = 1
35 243

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Solution :
(a) Example
The nth 3 : 2 n-1
term,
Tn = 2 n -1
The nth term of a sequence 3 Tn =
The first four terms of the sequence 3
are
( a ) Show2 ,that2 it 2is, a 2geometric
3 progression
, ...
1, 3 3 3 256
( b ) Find the value of n where T n =
T2 2 6561
3
r1 = = = 2
1 3 2
Since, Tthe common ratio, r =
1
3
2 2
T3
Thus the sequence is3a geometric progression
2
r2 = =
2
=
3
T2 3
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
(b) T = 256 , a = 1 and r =2
n
6561 3

256 = ( 1 ) 2 n-1

6561 3

2 n-1
= 2 8

3 3

n- 1 = 8
n = 9

## ∴ 256 is the 9th term

6561
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
The Sum of Geometric Sequence

A Geometric Sequence is
a , a r , a r 2 , a r 3 , . . . , a r n-2 , a r n-1

## The sum of the first n terms of a GS as Sn,

it follows that
S n = a + a r + a r 2 + a r 3 + . . . + a r n-2 + a r n -1

Multiplying by r givens

r S n = a r + a r 2 + a r 3 + a r 4 + . . . + a r n-1 + a r n
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Subtracting ,
Sn - rSn  
n2 n 1
 a  ar  ar 2
 ar 3
 ...  ar  ar
  ar  ar  ar  ...  ar
2 3 n 1
 ar n

S n  S n1  a  ar n

 Sn  1  r   a  1  r n

If r < 1 , Sn = a ( 1 - r n
) and
( 1 - r)

If r > 1 , Sn = a ( r n
- 1)
( r - 1)
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Solution 4: :
Example

a = 27 , r =2 (r < 1 )
Find S 5 of the3Geometric Series in
which
S n = a ( 21 - r )
n
Using
3
a = 27 and r =1 - r )
(

27 1 - 2
5

3
S 5 = = 70 1
3
1 - 2
3

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
4 = 631
n

Solution : 3 81
Example 5 :
a = 27 , r =4 n log 4 = log 631
3 3 81
The first
Suppose S n term
= 550of a Geometric Series is 27 and
log 631
a ( r n - 1 ) = 550 4 . Find the least number
81
itsr common
- 1 ration is 3 n =
of 4termsn the sequence can have if its
logsum4
27 - 1 3
3
exceeds 550 = 550 n = 7.136
4 - 1
Thus, for S n > 550, we require n > 7.136.
3
∴ n =n 8
4 - 1 = 550
3 81
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Geometric Mean
If a number b is inserted between a pair of numbers
a and c such that a, b, c are in Geometric Sequence,
then b is said to be the geometric mean of a and c.
It follows that
b = c
a b
or b 2 = c a
b =  √c a

## Note : For any three consecutive terms of a GS,

the middle term is the geometric mean
of the other two and is equal to the square
root of their product.
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Example 1 :

## Find the geometric mean of each of the

Following pairs of numbers :

(a) 4 , 16

(b) 8 , 18

(c) 1 1 , 5
4
(d)
1 3 , 7
4

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Solution :

( a ) Geometric mean = √( 4 ) ( 16 )
( c ) Geometric mean = √ ( 5 / 4 ) ( 5 )
=
=  28 . 5

( b ) Geometric mean  = √ ( 8 )
Geometric mean = √ ( 7 / 4 ) ( 7 )
( d () 16)
=  3 . .53137
= 11

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Sum To Infinity of a Geometric Sequence
Proof :
The sum
sum to
of the firstofna terms of a geometric sequence
The
Notice thatinfinity
the proof of Geometric
this result Sequence
is valid is–given
for 1 < r by
is given by ,
<1
∞S n = a 1 – r n

S∞ = Σ a r n - 1 = 1 a- r , l r l < 1
1-r
. n =
If - 1 < r < 1 then as n → ∞ , r n → 0
If this is not the case,
1 the sum to infinity does not exist.
The sum to infinity ofasa GS
Therefore, n →in∞which
, -1 < r <1 is given by,

S 1=– 0 a a
∴ S = a∞ =
1 - 1r - r 1 - r

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Example 2 :

## Calculate the sum to infinity of the series

2 + 1 + 1+ 1 + ...
2 8 32
Solution :
1
a = 2 and r =
4
Therefore ,
2
S∞ = = 8
1 -1 3
4

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Example 3 :

## the first term is 500 and common ratio2 ?

5
( b ) The sum to infinity of a GP is 90.

## If the common ratio is 3 , what is the

5
first term?

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Solution :
(b) S ∞ = a
1 - r
(a) S∞ = a a
1 - r 90 =
1 - 3
500 5
= a
1 -2 = 2
3 5
500 2
= a = 90
3 5
5
∴ a = 36
= 833 1
3
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Example 4 :

## first two terms is 48. Show that the common ratio,

7
r, satisfies the equation 1 - 49 r 2
= 0.

## Hence find the first term of the GP with positive

common ratio.

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Solution :

## The sum to infinity is 7,

a = 7
1 - r
a = 7(1 - r) ................. (1)

## The sum of the first two terms is 48

7
48
a + ar =
7
48
a (1 + r) = ................. (2)
7

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
Substituting (1) into (2) gives

7 ( 1 - r ) ( 1 + r ) 48
=
7

49 ( 1 - r 2
) = 48

49 - 49 r 2
= 48

Therefore 1 - 49 r 2
= 0

1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21
1 - 49 r 2 = 0
(1 + 7r) (1 - 7r) = 0
Therefore r = 1 or r = - 1
7 7
Since we require the GP with positive common ratio
1 , from (1) the first term is given by
r=
7
a = 7(1 - r)
a = 7 1 - 1
7
∴ a = 6
The first term of the GP with positive common ratio is 6
1 2 3 4 5 6 7 8 9 10 11

12 13 14 15 16 17 18 19 20 21